Particle formation and micronization using non-conventional techniques- review - Karim, Fahim Tamzeedul; Sarker, Md. Zaidul Islam; Abu Bakar, Mohd Rushdi; U.M., Salim; Awang, Mohamed; Ferdosh, Sahena; Khan Chowdhury, Ahmed Jalal; Sharif, K. M.; Hossain, Md Sohrab (Elsevier B.V, 2014)
Due to growing concerns regarding health, safety and the environment, non-conventional methods for particle formation and micronization that are either solvent-less or use environmentally acceptable solvents such as carbon dioxide have come into favor. Supercritical CO2 (sc CO2) (T > 31.1 'C, P > 7.3 MPa) has been used in food and pharmaceutical industries to minimize the use of organic solvents, produce new food products, produce environmentally superior food products and to process and micronize (0.1–5mm) pharmaceuticals. Control of particle size increases the dissolution rate of drugs into the body. Techniques that use sc CO2 eliminate inherent drawbacks of conventional methods such as thermal or mechanical degradation of the product, poor control of the particle size and morphology, lack of brittleness of some polymers and low encapsulation efficiency. Severaltechniques have been reported for the particle formation and micronization using supercritical fluids that have been successfully scaled up for commercial use. Supercritical CO2 has also been used to develop applications for medicines, essential oils, vitamins, food grade polymers, catalysts and pigments. This review highlights the process mechanism of supercritical fluid based techniques as well as some applications on particle formation and micronization.